Data warehousing and knowledge discovery : 7th International Conference, DaWak 2005, Copenhagen, Denmark, August 22-26, 2005 : proceedings - International Conference on Data Warehousing and Knowledge Discovery; Tjoa, A Min; Trujillo, Juan (Lecture Notes in Computer Science, 2005)
This book constitutes the refereed proceedings of the 7th International Conference on Data Warehousing and Knowledge Discovery, DaWak 2005, held in Copenhagen, Denmark, in August 2005. The 51 revised full papers presented were carefully reviewed and selected from 196 submissions. The papers are organized in topical sections on data warehouses, evaluation and tools, schema transformations, materialized views, aggregates, data warehouse queries and database processing issues, data mining algorithms and techniques, association rules, text processing and classification, security and privacy issues, patterns, and cluster and classification.